Encyclopedia of fundamentalism - Brasher, Brenda E., 1952- (New York : Routledge, 2001)
Follows a broad definition of fundamentalism and covers fundamentalism across time and place, although the emphasis remains on its primary manifestation: Protestant fundamentalism in the United States.
"A Berkshire Reference work."
Includes bibliographical references and index.
Keywords: Fundamentalism -- Encyclopedias